3D Printed Clamps for In Vitro Tensile Tests of Human Gracilis and the Superficial Third of Quadriceps Tendons - Ivan Grgić; Vjekoslav Wertheimer; Mirko Karakašić; Željko Ivandić (Applied Sciences, 2021)
Recent soft tissue studies have reported issues that occur during experimentation, such as the tissue slipping and rupturing during tensile loads, the lack of standard testing procedure and equipment, the necessity for existing laboratory equipment adaptation, etc. To overcome such issues and fulfil the need for the determination of the biomechanical properties of the human gracilis and the superficial third of the quadriceps tendons, 3D printed clamps with metric thread profile-based geometry were developed. The clamps’ geometry consists of a truncated pyramid pattern, which prevents the tendons from slipping and rupturing. The use of the thread application in the design of the clamp could be used in standard clamping development procedures, unlike in previously custom-made clamps. Fused deposition modeling (FDM) was used as a 3D printing technique, together with polylactic acid (PLA), which was used as a material for clamp printing. The design was confirmed and the experiments were conducted by using porcine and human tendons. The findings justify the usage of 3D printing technology for parts manufacturing in the case of tissue testing and establish independence from the existing machine clamp system, since it was possible to print clamps for each prepared specimen and thus reduce the time for experiment setup.